The Role of the Music Teacher as a Motivator - Lobenwein, Lea (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the role of the music teacher as a motivator, emphasizing their crucial part in fostering students' interest in music and enhancing their achievements. Through their dedication, teaching methods, and understanding of students' psychological needs, music teachers have a significant impact on motivation, engagement, and sustained interest in music. The central theme of the chapter is the variety of motivational strategies teachers can use to encourage musical development. These include creating a supportive learning environment, promoting collaborative creation and improvisation, providing tailored feedback, and cultivating intrinsic motivation. Special emphasis is placed on the teacher-student relationship, as a positive and supportive approach enhances students' confidence, perseverance, and enjoyment in learning music.